2008
DOI: 10.1042/cs20070393
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated differences in acetylcholinesterase activity in bronchial aspirates from patients with lung cancer

Abstract: In non-neuronal contexts, ACh (acetylcholine) is thought to be involved in the regulation of vital cell functions, such as proliferation, differentiation, apoptosis and cell-cell interaction. In airways, most cells express the non-neuronal cholinergic system, each containing a specific set of components required for synthesis, signal transduction and ACh hydrolysis. The aim of the present study was determine the expression of cholinergic system components in bronchial aspirates from control subjects and patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
5
18
0
Order By: Relevance
“…1C), meningioma [37], breast [36], and colon [30], and the observation of butyrylcholinesterase mRNA in kidney (Fig. 4), colon [30], and cancerous cell lines [39], support the idea of butyrylcholinesterase synthesis in the organs themselves. Nevertheless, the great quantity of butyrylcholinesterase activity in blood plasma [40] might lead us to think that renal butyrylcholinesterase arises totally or in part from blood.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…1C), meningioma [37], breast [36], and colon [30], and the observation of butyrylcholinesterase mRNA in kidney (Fig. 4), colon [30], and cancerous cell lines [39], support the idea of butyrylcholinesterase synthesis in the organs themselves. Nevertheless, the great quantity of butyrylcholinesterase activity in blood plasma [40] might lead us to think that renal butyrylcholinesterase arises totally or in part from blood.…”
Section: Discussionmentioning
confidence: 65%
“…The presence of acetylcholinesterase‐T mRNA in kidney (Fig. 4) contrasts with the absence of catalytic acetylcholinesterase‐T protein from kidney and cancerous cell lines of lung, breast, and gut [39], a feature that might be attributed to microRNA‐induced translational repression of the acetylcholinesterase‐T mRNA in epithelial cells. In this respect, there is evidence of a regulatory role for microRNA‐132 in the expression of acetylcholinesterase in leukocytes [44], but other reasons may exist, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez-Moreno has similarly reported that cholinesterase levels are reduced in lung cancer, thus increasing the available ACh to stimulate tumor growth (de Martinez-Lopez et al 2008; Martinez-Moreno et al 2006). …”
Section: Muscarinic Receptors and Specific Cancersmentioning
confidence: 99%
“…Several lines of evidence suggest that cholinesterases may be involved in tumour development: AChE and BChE are believed to play a role in cell proliferation and differentiation (37), cholinesterase genes have been found to be structurally altered or their products aberrantly expressed in tumours from a variety of tissues (3840) and AChE has been shown to support anchorage-independent growth of tumour cells in vitro (41). Ectopic alkaline phosphatase expression has been found in tumours of the lung, testis, fallopian tube and gastrointestinal tract (42).…”
Section: New Research To Improve the Objectivity And Mechanistic Undementioning
confidence: 99%